On methods for converting exhausters of positively homogeneous functions. (3rd March 2016) - Gorokhovik, Valentin V.; Trafimovich, Marina A.
Abstract : In the paper we develop a method for converting a (not necessarily uniformly bounded) upper (lower) primal exhauster of a continuous positively homogeneous function to a lower (upper) primal exhauster of the same function. The method is based on representation of a continuous positively homogeneous function as a pointwise supremum (infimum) of an one-parameter monotone family of Lipschitz continuous positively homogeneous functions that is of independent interest.